Antinociceptive activity of petroleum ether fraction obtained from methanolic extract of Clinacanthus nutans leaves involves the activation of opioid receptors and NO-mediated/cGMP-independent pathway - Zakaria, Zainul Amiruddin; Abdul Rahim, Mohammad Hafiz; Mohd Sani, Mohd Hijaz; Omar, Maizatul Hasyima; Ching, Siew Mooi; Abdul Kadir, Arifah; Ahmed, Qamar Uddin (BioMed Central Ltd, 2019)
Background Methanol extract (MECN) of Clinacanthus nutans Lindau leaves (family Acanthaceae) demonstrated peripherally and centrally mediated antinociceptive activity via the modulation of opioid/NO-mediated, but cGMP-independent pathway. In the present study, MECN was sequentially partitioned to obtain petroleum ether extract of C. nutans (PECN), which was subjected to antinociceptive study with aims of establishing its antinociceptive potential and determining the role of opioid receptors and l–arginine/nitric oxide/cyclic-guanosine monophosphate (l–arg/NO/cGMP) pathway in the observed antinociceptive activity.